The silent corner : a novel of suspense - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2017)
"I very much need to be dead." These are the chilling words left behind by a man who had everything to live for--but took his own life. In the void that remains stands his widow, Jane, surrounded by questions destined to go unanswered ... unless she does what all the grief, fear, confusion, and fury inside of her demands: find the truth, no matter what.
Keywords: Fugitives from justice -- Fiction; Truth -- Fiction; Psychological fiction